The Curriculum and Procedure in the Book (Foshat Al-Nass) By Dr. Abdul Azim Al-Sultani - Al-Janabi, Dr. Hassan Ghanem Fadala (International Journal of Psychosocial Rehabilitation, 2020)
This research represents an attempt in the field of applied criticism of literary criticism, as it took for itself a model represented in the book “The Space of Text. The Critical Empowerment in Modern Poetic Text” written by Dr. Abdul Azim Al-Sultani. The research has taken upon itself to consider this book in terms of the approach used in authorship as well as the mechanisms of critical treatment and their strategies, the book falls into five chapters embodying five critical readings of five poetry texts of varying size and subject matter and the technical nature of this or that text, which is reflected in the nature of Those readings in terms of method and procedural treatment, it became possible to describe those readings as free tourism - to some extent - approach and procedure. And we say: to a certain extent. Because these readings were not random or spontaneous in adopting a method and inserting it into this or that text, but rather took for itself the strategy of choosing the appropriate method for the text from the text itself and its nature and returning to it in a way that contributes to revealing its semantic dimensions and Content, but rather going further than that of its possibilities and potentials in a very conscious and purposeful manner methodology of research, because it has drawn for itself two methods of treatment and the nature of reading, one of which is comprehensible reading when the textual capabilities and its networks (semantic, content and aesthetic) are subject to accountability and critical deconstruction, and the second reading It focuses on the reality of what you find a central giveaway, leading his accountability and the manifestation of his truth to show the areas of enjoyment and benefit in this text or that.